SPRING: an RCT study of probiotics in the prevention of gestational diabetes mellitus in overweight and obese women - Nitert Marloes Dekker; Barrett Helen L; Foxcroft Katie; Tremellen Anne; Wilkinson Shelley; Lingwood Barbara; Tobin Jacinta M; McSweeney Chris; O'Rourke Peter; McIntyre H David; Callaway Leonie K (BMC, 2013)
Abstract Background Obesity is increasing in the child-bearing population as are the rates of gestational diabetes. Gestational diabetes is associated with higher rates of Cesarean Section for the mother and increased risks of macrosomia, higher body fat mass, respiratory distress and hypoglycemia for the infant. Prevention of gestational diabetes through life style intervention has proven to be difficult. A Finnish study showed that ingestion of specific probiotics altered the composition of the gut microbiome and thereby metabolism from early gestation and decreased rates of gestational diabetes in normal weight women. In SPRING (the Study of Probiotics IN the prevention of Gestational diabetes), the effectiveness of probiotics ingestion for the prevention of gestational diabetes will be assessed in overweight and obese women. Methods/design SPRING is a multi-center, prospective, double-blind randomized controlled trial run at two tertiary maternity hospitals in Brisbane, Australia. Five hundred and forty (540) women with a BMI > 25.0 kg/m2 will be recruited over 2 years and receive either probiotics or placebo capsules from 16 weeks gestation until delivery. The probiotics capsules contain > 1x109 cfu each of Lactobacillus rhamnosus GG and Bifidobacterium lactis BB-12 per capsule. The primary outcome is diagnosis of gestational diabetes at 28 weeks gestation. Secondary outcomes include rates of other pregnancy complications, gestational weight gain, mode of delivery, change in gut microbiome, preterm birth, macrosomia, and infant body composition. The trial has 80% power at a 5% 2-sided significance level to detect a >50% change in the rates of gestational diabetes in this high-risk group of pregnant women. Discussion SPRING will show if probiotics can be used as an easily implementable method of preventing gestational diabetes in the high-risk group of overweight and obese pregnant women.